IMPLEMENTASI PEMBELAJARAN BLENDED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Afrida Hanum; Nena Puspita Sari; Siti Rahmatina (Jurnal Dedikasi Pendidikan, 2023)
This study aimed to determine the effect of the implementation of blended learning to improve the learning outcomes of primary school students. The method used is quasi-experimental method with quantitative approach. The research design used was "Pretest-Posttest Non-Equivalent Control Group Design." This design uses two classes consisting of experimental and control class. The research was conducted on fourth-grade students of SD Negeri 1 Lambheu, District of Aceh Besar. The research sample amounted to 60 students. Data collection techniques in this study by giving pretest and posttest questions in both classes. The questions used are ten questions in form of multiple choice. The data analysis technique uses student learning outcomes data with normality and homogeneity testing; then, the hypothesis is tested using t-test. Based on testing, the value of student learning outcomes is normally distributed and homogeneous. The results of the t-test of posttest values were obtained by Sig. (2-tailed) = 0.00 < 0.05 then H0 is rejected and Ha is accepted. The hypothesis test concludes that there is a significant difference in the learning outcomes of the experimental and the control class students. As conclusion is that implementing blended learning to improve student learning outcomes of Primary SchoolKeywords : Blended Learning, Learning Outcomes, Primary School.